1) 2 (x-4) + 3 (2x+7) = 12
2) 4 (5-3x) -5 (3x+2) = 8- 6x
3) -5 (2x+3) + 3 (4x-2) = 2x -2
4) 7 (x-3) - 2 (2x+1) = 5 (4-3x)

Pouvez vous m'aider à faire cette exerciçe s'il vous plaît ces pour demain et je n'ai pas encore commencé. Merci d'avance

1

Réponses

2013-11-04T18:48:53+01:00
1) 2 (x-4) + 3 (2x+7) = 12
2x-8+6x+21=12
2x+6x=12-21+8
8x= -1
x= -1/8

2) 4 (5-3x) -5 (3x+2) = 8- 6x 
20-12x-15x-10=8-6x
-12x-15x+6x=8+10-20
-21x=-2
x=2/21

3) -5 (2x+3) + 3 (4x-2) = 2x -2
-10x-15+12x-6=2x-2
-10x+12x-2x=-2+6+15
0x=19
x=0

4) 7 (x-3) - 2 (2x+1) = 5 (4-3x) 
7x-21-4x-2=20-15x
7x-4x+15x=20+21+2
18x=43
x=43/18